Screen time and working memory in adolescents: A longitudinal study. (May 2021) - Soares, Pedro San Martin; de Oliveira, Paula Duarte; Wehrmeister, Fernando César; Menezes, Ana Maria Baptista; Gonçalves, Helen
Abstract: Little is known about the effects of excessive screen time on Working Memory (WM) in adolescents. The aim of this study was to investigate the association between measures of screen time in adolescence and Working Memory. Data from the 1993 Pelotas (Brazil) Birth Cohort Study were analyzed (N = 3625). Self-reported screen time was collected at ages 11, 15 and 18. Working Memory performance (Digit Span backward score) was examined at age 22. Multiple linear regression was used to assess the associations between three screen time measures (television, video game and computer time) for each age and WM at age 22. We also evaluated the direct and indirect effect by mediation analysis, using the intelligence quotient (IQ) at 18 years as mediator. In men, television and video game time at 11 years and computer at ages 11 and 15 years had a positive effect on WM. Also, these effects were mediated through IQ. In women there was no significant association between screen time measures at ages 11, 15, and 18 and WM. This study provides new insights about the relationship between television, videogame, and computer time with WM in adolescents, by exploring the paths of these associations and considering the important mediating role of IQ.